2000
DOI: 10.1093/toxsci/54.1.104
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Antioxidants on Cigarette Smoke-Induced DNA Single-Strand Breaks in Mouse Organs: A Preliminary Study with the Alkaline Single Cell Gel Electrophoresis Assay

Abstract: According to published information, the lung is the only clear target organ for tumors when mice are exposed to cigarette smoke. Liver, skin, and upper digestive tract are target organs when orally or dermally exposed to cigarette smoke condensate, but not kidney, brain, or bone marrow. We tested the genotoxicity of cigarette smoke in the known target organ (lung), possible target organs (stomach and liver), and non-target organs (kidney, brain, and bone marrow) of the mouse using the alkaline single-cell gel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
28
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 24 publications
4
28
0
Order By: Relevance
“…EA is a phenolic lactone that exerts its anticarcinogenic and antimutagenic activities through several mechanisms, including scavenging reactive oxygen species (30,57,58). This observation is in agreement with previous studies investigating the antioxidant activities of EA on DNA strand breaks (59,60). Our data suggest that CSC-induced DNA strand breaks may, in part, originate from free radicals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…EA is a phenolic lactone that exerts its anticarcinogenic and antimutagenic activities through several mechanisms, including scavenging reactive oxygen species (30,57,58). This observation is in agreement with previous studies investigating the antioxidant activities of EA on DNA strand breaks (59,60). Our data suggest that CSC-induced DNA strand breaks may, in part, originate from free radicals.…”
Section: Discussionsupporting
confidence: 92%
“…Based upon our findings, we speculate that there may be two possible explanations for the lack of attenuation of basal levels of DNA strand breaks. First, cigarette smoke contains more than 5,000 chemicals with diverse interactions (60), which may influence the effectiveness of EA to act as an antioxidant. Second, in our laboratory, it has been reported that EA was a potent inhibitor of dibenzo[a,l]pyrene-DNA adducts in a microsome-mediated test system by ≄75% (61).…”
Section: Discussionmentioning
confidence: 99%
“…In general, CS leads to apoptosis by means of oxidative stress, mitochondrial and nuclear damage, and TNF receptor signaling (Tsuda et al, 2000;Carnevali et al, 2003;Tuder et al, 2003). CS-induced single strand DNA break by acute CS exposure is caused by stimulation of free radicals (Tsuda et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, the time between last exposure and dissection might have been too long. It has been reported, although under rather different smoke exposure conditions (1-min exposure and extremely high smoke concentration), that the level of DNA strand breaks in the lung returns to control values already after 1 hour (69). In vitro, cigarette smoke is clearly active (70).…”
Section: Discussionmentioning
confidence: 96%
“…Both studies found a positive effect, however, despite the high smoke concentrations (dilution around 1/7, in our study 1/100), the short daily exposure times (10 min and 1 min, respectively) resulted in lower daily inhalation doses (time × concentration). Theoretical doses were 75% and 10%, respectively (73,69); however, it can be assumed that the actual doses were significantly lower, as rodents, if briefly exposed, are known to lower their respiratory minute volume drastically as a function of the irritative potency of the inhalant (74). A further explanation for the failure of the Comet assay to show smoke-related responses in our study could be the cross-linking effect of aldehydes in smoke, which can inhibit DNA migration preventing the detection of increases in strand breaks in the assay (72,75).…”
Section: Discussionmentioning
confidence: 99%